1998
DOI: 10.2307/1132080
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence, Social Support, and Attachment: Demarcation of Construct Domains, Measurement, and Paths of Influence for Preschool Children Attending Head Start

Abstract: Two studies designed to (1) explore measurement issues for the construct domains of social competence and social support and (2) test a model relating social competence to social support and to child-parent attachment for low-income (primarily African American) preschool children attending Head Start are reported. In Study 1, the definition, measurement, and structure of the social competence construct are evaluated in 2 samples of children. For Study 1A, 167 4-year-old children were assessed with a battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
1
30
0
3
Order By: Relevance
“…Some arise from our use of data collected for a different original purpose. For example, the original study was a developmental study of social competence and its correlates in a sample of children attending Head Start (Bost et al 1998). Had we envisioned these analyses, we would have recruited a larger sample of mixed-age classrooms and made certain that they were observed at all time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some arise from our use of data collected for a different original purpose. For example, the original study was a developmental study of social competence and its correlates in a sample of children attending Head Start (Bost et al 1998). Had we envisioned these analyses, we would have recruited a larger sample of mixed-age classrooms and made certain that they were observed at all time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using these observation protocols has demonstrated that observers quickly reach agreement rates of 80% and above for visual regard recipients with only limited training (Bost et al 1998;Vaughn and Martino 1988;Waters 1980, 1981;Waters et al 1983). For this study, training typically took less than 90 min and no observer failed to achieve 80% agreement with a partner in live observations.…”
Section: Visual Regard Observationsmentioning
confidence: 99%
“…Several studies have linked early insecure attachment to poorer peer relationships, lower social competence, and more aggression [Bost et al, 1998;Fagot and Kavanagh, 1990;Lyons-Ruth, 1996;LaFreniere and Sroufe, 1985]. A limited amount of research has looked at the relationship between bullying and victimisation, and attachment directly.…”
Section: Correlates Of Roles In Victimisationmentioning
confidence: 99%
“…Waters e Sroufe (1983), assim como Rose-Krasnor (1997), definem o constructo da competência social considerando, em simultâneo, a coordenação fl exível de afetos, comportamentos e cognições, que resultarão na capacidade do indivíduo: (a) concretizar, de facto, os seus objetivos sociais; (b) sem limitar, excessivamente, as oportunidades dos parceiros obterem os seus próprios objetivos sociais; (c) minimizando/impedindo o progresso de trajetórias de desenvolvimento que restrinjam opções futuras na obtenção dos objetivos sociais, as quais não podem ser identifi cadas no presente. Nesta perspetiva, Bost, Vaughn, Washington, Cielinski, e Bradbard (1998) bem como , sugerem a necessidade de se analisar três facetas relevantes para o sucesso social das crianças em idade pré-escolar, nomeadamente: a motivação para o envolvimento social, a aceitação dos pares e os perfi s de competências, traços, atitudes e crenças. Pressupõem os autores, que difi culdades numa destas dimensões, implicará difi culdades para os sujeitos negociarem os desafi os que se colocam num grupo social de crianças nestas idades.…”
unclassified
“…Para o efeito, é utilizada uma taxonomia de análise distinta da de Rubin (2001) mas baseada, também, na observação das crianças em diferentes momentos do seu dia-a-dia no Jardim-de-Infância, nomeadamente: a medida de Envolvimento Social (eg., Bost et al, 1998;Santos, Vaughn, Bost, 2008;Santos et al, 2014). Esta inclui observações diretas de três indicadores: atenção visual recebida e interações positivas e neutras iniciadas pelo sujeito.…”
unclassified